Basic analysis III : mappings on infinite dimensional spaces - Peterson, James K. (James Kent) (Boca Raton : Chapman & Hall/CRC, 2020)
Basic Analysis III: Mappings on Infinite Dimensional Spaces is intended as a first course in abstract linear analysis. This textbook cover metric spaces, normed linear spaces and inner product spaces, along with many other deeper abstract ideas such a completeness, operators and dual spaces. These topics act as an important tool in the development of a mathematically trained scientist. Feature: Can be used as a traditional textbook as well as for self-study Suitable for undergraduates in mathematics and associated disciplines Emphasizes learning how to understand the consequences of assumptions using a variety of tools to provide the proofs of propositions
OCLC-licensed vendor bibliographic record.
Keywords: Functional analysis; Infinite groups; MATHEMATICS / Functional Analysis; MATHEMATICS / Applied